Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

S=L (1 - r), for r
This is all it says, you are solving for r, the instructions just say solve for r


Sagot :

AL2006
OK. Then let's solve for ' r '.  That means you have to come up with an equation that says     r =    everything else.

Step #1: 
Write the equation you're given:   S = L (1 - r)

Let's divide each side by ' L ':      S/L = 1 - r

Subtract 1 from each side :         S/L - 1 = -r

Multiply each side by -1 :            1 - S/L = r

and there you have it.